ANALYSIS OF THE FORMATION PROCESS OF SINJAB SLANG IN BATANG REGENCY - Sriatun, Sriatun; Winarti, Daru (Prologue: Journal on Language and Literature, 2024)
This research aims to classify the patterns and rules of Sinjab slang formation. Data collected were obtained from two native speakers of Sinjab slang. This research employs a sociolinguistic approach. The data analysis process is conducted using qualitative descriptive methods. Interviews and data collection were carried out with informants who are young adults aged 35 and 25. Furthermore, this study categorizes the data into tables to facilitate the data analysis process. The results of the research indicate that the Sinjab slang vocabulary is not formed arbitrarily. Based on the analyzed data, variations in Sinjab slang forms and the linguistic processes involved therein are phoneme shifts, commonly known as metathesis. The formation processes mapped include: a) phoneme shift (metathesis), b) phoneme shift (metathesis) accompanied by phoneme addition, c) phoneme shift (metathesis) accompanied by phoneme release, d) phoneme shift (metathesis) accompanied by phoneme replacement, e) absorption of foreign languages, and f) zero process. Based on the mapped formation processes, 15 Sinjab slang formation patterns are identified. These patterns include the K2V1K1V2 pattern., pattern K2V1K1V2K2, pattern K2V1mK1V2, pattern K2V1mK1V2K2, pattern K2V1ngK1V2, pattern K2V1ngK1V2K2, pattern K2V1K1V2ng, pattern K2V1nK1V2, pattern K2V1nK1V2K2, pattern K2V1ngkV2, pattern K2V1ngkV2, pattern K2V1ngkV2K2, pattern K1V1K2asgV2, Pattern K1V1K2asgV2K2, pattern K1V1K1K2asgV2, pattern K1V1K2askV2.